Pengaruh penggunaan gadget terhadap tumbuh kembang dan perilaku sosial anak dibawah umur - Tamam, Safira Putri (Maliki Interdisciplinary Journal, 2023)
This article is written to examine the effects of the use of gadgets on minors. This article is very important to examine to enhance insight for the readers. Gadget, or which is well known as smartphone is a form of technology advances. Gadgets now have become a major need for both adults and children. Apart from its main function as a communication tool, gadgets can also help humans to ease their activities. Nowadays, it is common for parents to introduce gadgets to their children. Therefore, it would be nice for parents to limit their children's use of gadgets, so their children can still have well development and still be active, intelligent and interactive children. Excessive use of gadgets or consumptive behaviour can affect children's social development and behaviour. Children will tend to limit themselves with their environment which causes a decrease in their ability to interact and socialize.